A Self-Forming Vessel: Aristotle, Plasticity, and the Developing Nature of the Intellect. Issue 51 (2nd July 2020) - Kislev, S. F.
ABSTRACT: Highlighting the relations between De Anima II.5 and De Anima III.4, this paper argues that Aristotle held a surprisingly dynamic view of the intellect. According to this view, the intellect is in a constant development brought about by its own activity. This dynamic view distinguishes the intellect from both physical objects and from sense-perception. For Aristotle the intellect is a "nothing" that gradually becomes something by thinking. The paper traces the logic of this idea and its meaning. It defends the simple thesis that in the intellect alone first and second transitions are bound together: that every concrete thought is also a determination of the possibility of the intellect. This, I will suggest, was known to ancient commentators who distinguished between not two but three "intellects" in De Anima; not only the possible and actual intellects, but also the acquired intellect. It is the unique conceptual structure of the acquired intellect that this paper sketches.